Multiscale Glass Fiber/Epoxy Nanocomposites Incorporated with Graphene and Zinc Oxide Nanoparticles: Enhanced Mechanical Properties - Barshan Dev; Shah Ashiquzzaman Nipu; Md Ashikur Rahman; Khondokar Raihan Mahmud; Maksudur Rahman Riyad; Md Zillur Rahman (Macromolecular Materials and Engineering)
Abstract This study fabricates multiscale glass fiber/epoxy composites by incorporating graphene nanoparticles (GNPs) and zinc oxide nanoparticles (ZnO NPs) to investigate the influences of NPs on the mechanical properties of composites. The composites are manufactured using the compression molding technique with different GNP contents (i.e., 0, 0.5, 1, and 1.5 wt.%), whereas the contents of glass fibers and ZnO NPs remained the same at 40 and 4 wt.%, respectively. Their mechanical properties, chemical compositions, and fracture morphologies are then evaluated. It is found that the mechanical properties of composites improve significantly at a lower content (i.e., 0.5 wt.%) of GNPs and tend to decrease at higher contents (i.e., 1 and 1.5 wt.%). The composite is composed of 0.5 wt.% GNPs exhibit maximum tensile modulus and strength of 6.74 GPa and 230.25 MPa, and flexural modulus and strength of 16.43 GPa and 831.79 MPa, respectively, impact strength of 47.25 kJ m−2, and maximum hardness (97.96 Shore D), among all nanocomposites. Moreover, fracture morphologies reveal that composite failure is predominately caused by fiber breakage, fiber‐matrix debonding, voids, and GNP agglomeration. The outcomes of this study provide some insights to promote the application of manufactured multiscale composites in the aerospace, automotive, and marine industries.